Penerapan Multimedia untuk Meningkatkan Aktivitas dan Hasil Belajar Pendidikan Agama Hindu pada Siswa Kelas III SD Negeri 2 Tejakula - Suardeyasa, I Gusti Nyoman; Laksana Utama, Putu Kussa (Institut Hindu Dharma Denpasar, 2019)
Based on preliminary data, out of 24 students showed low student learning activities. And only 6 students who have successfully completed grades above KKM 75. This study was designed with Two Cycles namely Cycle I and Cycle II, the method of data collection was carried out by observation, test and literature study. Data were analyzed by descriptive statistical analysis. The results of the study were achieved in the pre-cycle of facitious students in learning and even minimal in the activity of skills, in the first cycle students in the less active category were 33.3%, quite active was 44.4%, and those already in the active category in learning were 22.2 %. In the second cycle, there was a significant increase, namely 20.8% of students were in the quite active category 19.4%, 27.8% active category and 58.8% very active category. the acquisition of student scores increased significantly, from 6 people (16.7%) getting 75 increased in cycle I to 22 (61.1%) and in cycle II increasing to 36 people (100%) achieving mastery learning grades above KKM 75. The application of multimedia can be used effectively in increasing student activity and learning outcomes in class III SDN 2 Tejakula.